PERAN IBU DALAM PENDAMPINGAN MENONTON TELEVISI PADA ANAK USIA 4-6 TAHUN DI DUSUN CANGKIR DESA CANGKIR KECAMATAN DRIYOREJO KABUPATEN GRESIK - Indatul Laili, Siti; Lidiawati, Kiki (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Accompany the child when watching television is very important because it makes children more comfortable while watching television, enhance the emotional connection between parents and children, And Right Selection Events for Children. The purpose of this research was to knowing the role of mothers in caring watching television in children age 4-6 years in Cangkir hamlet, Cangkir Village, Driyorejo District of Gresik. The research design used deskriptif. The population in this research are all mothers of children age 4-6 years in Cangkir hamlet, Cangkir Village, Driyorejo District of Gresik a number of 38 respondents. The sampel was all mothers of children age 4-6 years in Cangkir hamlet, Cangkir Village, Driyorejo District of Gresik a number of 38 respondents. with total sampling teckhnic. The instrument in this research used kuesioner. The time of this research 14 August 2016. Analyzing data used was tabel frekuensi distribution. The results showed that Most respondents have a negative role as much as 23 respondents (60.5%). This shows the role of mothers to provide an overview and consideration of positive and negative values when children watch television so that children are able to take the best decision.Keyword: Role Mothers, Television , Children age 4-6 years